DARI ‘ABID AL-JABIRI TENTANG EPISTEMOLOGI ARAB ISLAM - Hasan Mahfudh (Dialogia: Islamic Studies and Social Journal, 2015)
Abstract: To deal with modernity, al-Ja>biri> offered an alternative reading mothods which was then called Qira>'ah mua's}irah (contemporary readings) with its characteristics ja'lu al-maqru>' mu'a>s}ir li>nafsih wa mu'a>s}ir lana>. The method is defined into two steps: first, fas}l al-maqru>' 'an al-qa>ri> (subject took distance from the object study to obtain objectivity), second, was}l al-qa> ri> ' an al-maqru> '(the subject has a link himself with the object of study in order to actualize and measure the relevance of the present subject). Furthermore, al-Ja>biri> concluded that Arabic reasoning divided into three epistemological systems, first indication system (baya>ni> epistemology) is a system that first appeared in Arab thinking. Nevertheless, al-Ja>biri> considered that this epistemology is strongly influenced by Badui (a'rabi>} so that it is not excessive called as hegemony, thus allowing it to be criticized. Second, 'Irfa>ni> system ('Irfa>ni>’s epistemology}) in which knowledge is acquired through God exposure to His slaves (Kashf}) after the spiritualists (riya>d}ah). Departing from here, al-Ja>biri> actually scientific obtained in this way failing to provide a convincing conclusion. Third, the burha>ni’s system (burha>ni> epistemology) in which al-Ja>biri> is very skewed vision him- emphasized the innate potential source of knowledge is reasonable. Nevertheless, there are opposition who judge that al-Ja>biri> inconsistency against his own behavior, one hand he refused Marxist reading style of tura>ts, but on the other hand, the way he criticized 'Irfa> ni> and prioritized Burhani, then it is considered to be Marxist models. However, there are some scientists who considered that the discovery of al-Ja>biri> is one form of methodological revolution in reading tura> ts, the readings epistemologically useful to articulate the gap tradition (tura> ts) and modernity.Keywords: Tradisi (Tura>th), Qira>’ah Mu’as}irah, Baya>ni>, Burha>ni> dan ‘Irfa>ni>.